Influence of trace level As or Ni on pyrite formation kinetics at low temperature. (1st May 2021) - Baya, C.; Le Pape, P.; Baptiste, B.; Brest, J.; Landrot, G.; Elkaim, E.; Noël, V.; Blanchard, M.; Ona-Nguema, G.; Juillot, F.; Morin, G.
Abstract: Pyrite formation at low temperature during early diagenesis in (sub-)surface sediments is an essential step of Fe and S biogeochemical cycles and the presence of this ubiquitous mineral of surface environments is often used as an indicator of paleo-redox conditions. Pathways of pyrite formation are usually discussed in environmental settings by involving a variety of nanosized Fe-S mineralogical precursors as a function of the local geochemical conditions. However, the influence of trace element impurities such as Ni and As in the solution at the time of pyrite formation has been poorly studied, whereas specific chemical signatures of trace elements are commonly observed in sedimentary pyrites. A better understanding of the impact of Ni and As incorporation at trace levels on pyrite formation is essential to help refining the use of these elements as paleo-redox indicators and to evaluate the role of pyrite as a sink regulating the biogeochemical cycle of potentially toxic trace elements. In this study, we have performed syntheses of pyrite at low temperature via the polysulfide pathway using aqueous Fe(III) and H2 S in the presence of trace amounts of Ni(II) (0.001 mol%Fe) and As(III) (0.001 mol%Fe). Analysis of the solids collected at different time steps over the course of the experiments using X-Ray absorption spectroscopy at both the Fe and S K- edges shows that pyrite starts to precipitate within 5 days in presence of Ni(II) and within 32 days in presence of As(III), while the control experiment showed an intermediate precipitation rate of 14 days. Shell-by-shell analysis of Fe K- edge EXAFS data shows that the initial mineralogical precursors are the same in all the experiments and correspond to poorly-crystalline FeS (3.0 ± 0.1 Fe-S@2.25 Å; 1.7 ± 0.2 Fe-Fe@2.67 Å). In addition, XANES qualitative analysis suggests the incorporation of small amounts of Fe(III) within these FeS precursors. Synchrotron-based XRD and WAXS-PDF analysis of the starting solids show that in addition to S(0), the FeS precursors correspond to a continuum of FeS particles that ranges from tetragonal nanocrystalline FeS (a = 3.70(2) Å, c = 5.24(7) Å, MCDab  = 41 ± 4 Å MCDc  = 21 ± 2 Å) to cluster-type FeS (MCDabc  < 8.4 ± 4.3 Å). We propose that Ni(II) and As(III) have a different type of interaction with these FeS precursors, resulting respectively in an increase and a decrease in the rate of pyrite nucleation. While Ni(II) would incorporate within the structure of the FeS precursors, As would interact with (poly)sulfides in solution to form thio-As, possibly binding or precipitating onto FeS surfaces and thus slowing FeS transformation to FeS2 . Given that both Ni and As were introduced at trace levels in our experiments, these results suggest that the occurrence of trace amounts of impurities could have a strong influence on pyrite precipitation kinetics in natural settings such as pore-scale microenvironments. In addition to emphasizing the importance of trace elements such as Ni or As on the persistence of mobile colloidal FeS species in anoxic conditions, the results of the present study also point to the importance of considering the actual nature of the impurities when using pyrite composition for ancient environments and past climates reconstruction.